Effects of accelerated versus standard care surgery on the risk of acute kidney injury in patients with a hip fracture: a substudy protocol of the hip fracture Accelerated surgical TreaTment And Care tracK (HIP ATTACK) international randomised controlled trial. Issue 9 (24th September 2019) - Borges, Flavia K; Devereaux, P J; Cuerden, Meaghan; Bhandari, Mohit; Guerra-Farfán, Ernesto; Patel, Ameen; Sigamani, Alben; Umer, Masood; Neary, John; Tiboni, Maria; Tandon, Vikas; Ramokgopa, Mmampapatla Thomas; et al.
Abstract : Introduction: Inflammation, dehydration, hypotension and bleeding may all contribute to the development of acute kidney injury (AKI). Accelerated surgery after a hip fracture can decrease the exposure time to such contributors and may reduce the risk of AKI. Methods and analysis: Hip fracture Accelerated surgical TreaTment And Care tracK (HIP ATTACK) is a multicentre, international, parallel-group randomised controlled trial (RCT). Patients who suffer a hip fracture are randomly allocated to either accelerated medical assessment and surgical repair with a goal of surgery within 6 hours of diagnosis or standard care where a repair typically occurs 24 to 48 hours after diagnosis. The primary outcome of this substudy is the development of AKI within 7 days of randomisation. We anticipate at least 1998 patients will participate in this substudy. Ethics and dissemination: We obtained ethics approval for additional serum creatinine recordings in consecutive patients enrolled at 70 participating centres. All patients provide consent before randomisation. We anticipate reporting substudy results by 2021. Trial registration number: NCT02027896 ; Pre-results.